DRILLING CONTRACTOR HIRING SELECTION USING ANALYTIC HIERARCHY PROCESS (AHP) METHOD IN GEOTHERMAL WELL CONSTRUCTION PROJECT - Indrawan, Lavendo
COP28 (Climate Change Conference) in Dubai concluded with an agreement that marks the "beginning of the end" for the fossil fuel era. The agreement urges parties to take global action to triple renewable energy capacity and double progess in energy efficiency by 2030. Indonesia is believed to have the second largest geothermal energy potential in the world. However, the utilization as electricity generation is quite low compared to other countries which also have geothermal energy potential. Indonesia only utilizes approximately 10% of its total potential. Challenges come from the economic value of the project itself. The cost of global geothermal industry is primarily dominated by two key components: power plant construction and well construction. Well construction involves costly and timeconsuming operations, with drilling being the primary activity. The cost of drilling operations includes the use of existing drilling equipment and formation evaluation. Considering these factors, the well construction cost shall attempt to be reduced or at least managed to maintain the economic value of the project. This research aims to decide criteria that important for geothermal operators or project owner to select reputable and reliable drilling contractor (drilling rig). To determine the criteria and prioritization techniques, a literature study was conducted, along with interviews with key decision makers in the company, questionnaires to company experts, and a survey of industry practitioners. Four main criteria—administrative, HSE (Health, Safety, and Environment), technical requirements, and commercial—were identified to support the prioritization process using the Analytic Hierarchy Process (AHP). Among the fourteen subcriteria, the three with the highest global weights are HSE Performance, Rates, and the Well Control System